An evaluation of U.S. EPA aPCR methods at select Door County, WI beaches - Campbell, Aaron (My University, 2017)
The United States Environmental Protection Agency (EPA) has adopted numerous techniques for enumerating fecal indicator bacteria, each with varying advantages and disadvantages. Traditional culture techniques require 18-24 hours of incubation and do not provide results in a time sufficient manner to adequately protect public health. To help solve this issue, the EPA has developed rapid bacterial indicator methods based on real-time quantitative polymerase chain reaction (qPCR) technology. Some results from these rapid methods (calibrator cell equivalents, CCE) have shown to correlate with results from culture based methods (most probable number, MPN), accurately predicting risk for gastro-intestinal illness. However, there are no comparative studies that have been done in the Great Lakes or at beaches that are not directly impacted by human fecal contributions. In this study, Enterococcus qPCR Method 1609 and E. coli qPCR Method C were compared to the defined substrate methods Enterolert and Colilert, respectively, at four beaches in Door County, Wisconsin. Baileys Harbor beach does not exhibit any significant correlations (p>0.05) between the qPCR methods and defined substrate methods (r2=0.025 (Enterococcus) and 0.002 (E. coli)). Fish Creek beach shows a positive correlation between Enterococcus qPCR and culture methods (r2= 0.387. p<0.01), while method C does not show any significant correlation (r2=0.01, p>0.05). Otumba beach shows weakly positive correlations for both qPCR assays and their associated cultures (Enterococcus r2= 0.141 (p=0.0169), E. coli r2=0.363 (p<0.01). Correlations for Sunset beach have r2 values of 0.021 for Enterococcus (p>0.05) and 0.104 for E. coli (p=0.0307). In addition to the correlations, the agreement between methods was recorded and compared to current regulatory standards. If adopted as the regulatory method, qPCR methods would result in a minimum increase of beach closures of 10 percent and a maximum increase of 47 percent for either method. This suggests that qPCR would be more protective of public health than current culture based enumeration methods. These increases in beach closures may have potential social and economic ramifications in local communities. While it is clear much research is needed to distinguish which method is more appropriate for the Great Lakes Region and this study suggests a site by site evaluation of qPCR testing methods before they are adopted for use in monitoring recreational water quality.
A Thesis Submitted In Partial Fulfillment of the Requirements For the Degree of Master of Science-Biology in Microbiology
Keywords: Water quality; Beach closures--Wisconsin--Door County, Wisconsin; Enterococcal infections; Lakes--Recreational use; Enterococcus--Environmental aspects--Door County, Wisconsin.